Kepemimpinan di Sekolah Boarding School - Natasya Salsabilla Syarief; Fandi Akhmad; Hanifah Nur Erma; Dede Santika; Elisa Putri Kholifah (Peneliti.net, 2022)
A leader must have the soul of a leader, so that he can lead the institution, to achieve the desired goals. The success of the school cannot be separated from the leadership in the school. Now many schools have been established with the Boarding School System. Schools where students live in dormitories for 24 hours and are accompanied by teachers or coaches. Schools with the Boarding School System are located in Islamic Boarding Schools, where students study, and rest in Islamic boarding schools. The success of the Boarding School or Islamic Boarding School is achieved by the leadership in the school.